A Great Tit Parus major without yellow pigment in its plumage - Svensson, Sören; Kadin, Germund (Ornis Svecica, 2018)
A Great Tit Parus major without any yellow pigment in the plumage was ringed in southern Swedish Lapland in 2006. Such pale birds are known to appear with a low frequency throughout the species’ range. Superficially they look like the eastern (sub)species Parus (major) minor. The focal bird was a yearling with a wing length well above that of minor so there is no reason to suspect eastern origin. The yellow pigment, a carotenoid, is obtained through food, particularly green larvae. Such larvae were available in reasonably high numbers in 2006. The focal bird was an exception as no other pale Great Tit has been recorded during more than fifty years of fieldwork in the area. Yellow at the flange of the gape indicates that the bird had not completely lost its capacity to take up pig-ments, only the plumage was affected.